2006
DOI: 10.1007/s00439-006-0157-6
|View full text |Cite
|
Sign up to set email alerts
|

Parental and chromosomal origin of unbalanced de novo structural chromosome abnormalities in man

Abstract: We report the parental origin, and where possible the chromosomal origin of 115 de novo unbalanced structural chromosome abnormalities detectable by light microscopy. These consisted of 39 terminal deletions, 35 interstitial deletions, 8 rings, 12 duplications and 21 unbalanced translocations. In all categories the majority of abnormalities were of paternal origin, although the proportions varied from a high of 84% in the interstitial deletions and rings to a low of 58% in the duplications. Among the interstit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
42
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(48 citation statements)
references
References 16 publications
5
42
0
1
Order By: Relevance
“…18,19 In our series, only two of nine deletions in patients, for whom parental-origin data were obtained, were located in the maternal chromosome, which is consistent with the ratio reported previously for interstitial deletions at any site. 44 In another study, de novo imbalances not mediated by low copy repeats were significantly more often of paternal than of maternal origin. 45 Thus, to date, although there is no strong evidence supporting an imprinting mechanism in the 6q16 region, a parent-of-origin effect cannot be excluded, as none of the three maternally derived deletions, which were currently reported, (patient no.…”
Section: Clinical and Fetopathological Datamentioning
confidence: 94%
“…18,19 In our series, only two of nine deletions in patients, for whom parental-origin data were obtained, were located in the maternal chromosome, which is consistent with the ratio reported previously for interstitial deletions at any site. 44 In another study, de novo imbalances not mediated by low copy repeats were significantly more often of paternal than of maternal origin. 45 Thus, to date, although there is no strong evidence supporting an imprinting mechanism in the 6q16 region, a parent-of-origin effect cannot be excluded, as none of the three maternally derived deletions, which were currently reported, (patient no.…”
Section: Clinical and Fetopathological Datamentioning
confidence: 94%
“…Although base substitutions are the most frequent paternal genetic abnormalities, it is reported that 80 % of structural chromosomal abnormalities may originate paternally [83,124] ( Table 4). Several studies have suggested that chromosomal deletions and duplications increase with paternal aging [124].…”
Section: Effect Of Paternal Age On Other Diseasesmentioning
confidence: 99%
“…Several studies have suggested that chromosomal deletions and duplications increase with paternal aging [124].…”
Section: Effect Of Paternal Age On Other Diseasesmentioning
confidence: 99%
“…The majority of 115 de novo unbalanced structural chromosome abnormalities detectable by light microscopy are of paternal origin 4 varying from 84% of interstitial deletions to 58% of duplications and rings. Deletions of the long arm of chromosome 18 are disproportionately male 5 as well as the deletions that cause Wolf-Hirschhorn syndrome 6 and Cri-du-chat syndrome.…”
Section: Introductionmentioning
confidence: 99%